Performing feeding trial on broiler chicken using different ratios of protease treated black soldier fly (Hermetic Illucens) larvae as partial protein substituent - Rishaliney Selva, Rajoo (2020)
This project is about performing feeding trial on Broiler Chicken using different ratios of protease treated Black Soldier Fly (Hermetia Illucens) Larvae as partial protein substituent. It was an initiative taken to reduce the cost of production of broilers as well as to increase the survivability of the broilers. Thus, parameters set was to measure the growth rate, feed conversion ratio and mortality percentage of the broilers at the end of the project. Four different treatments was set up with inclusion of 0% BSFL meal that acts as control, 20% BSFL, 40% BSFL and 60% BSFL meal in the feed formulation. It was tested on 32 male Cobb broilers for 42 days. The results showed 20% BSFL treatment had better performance in all aspects as compared to other treatments including control. However, the results expected wasn't as high as expected due to several limitation factors such as anti-nutritional factor and chitin presence in the feed, broiler leg deformities, weather and machinery malfunction.